2022
DOI: 10.1371/journal.pone.0274106
|View full text |Cite
|
Sign up to set email alerts
|

PUMA screening tool to detect COPD in high-risk patients in Chinese primary care–A validation study

Abstract: The early stage of chronic obstructive pulmonary disease (COPD) is not easily recognized. Screening tools can help to identify high-risk patients in primary care settings for spirometry and may be helpful in the early detection in COPD and management. This study aims to validate the PUMA questionnaire for use in Chinese primary care settings. This cross-sectional study recruited participants (≥40 years old, current or former smoker with ≥10 packs of cigarette per year) in primary health care clinics in Hong Ko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
0
5
0
2
Order By: Relevance
“…established a cut-off value similar to the value proposed by a previous study [12], which had a sensitivity of 76.5% and specificity of 63.3%. The previous study showed that PUMA scores of ≥5 offered higher sensitivity (91.2%) but lower specificity (42.6%), influenced by factors such as age and smoking prevalence [12].…”
Section: Short Communicationmentioning
confidence: 69%
See 4 more Smart Citations
“…established a cut-off value similar to the value proposed by a previous study [12], which had a sensitivity of 76.5% and specificity of 63.3%. The previous study showed that PUMA scores of ≥5 offered higher sensitivity (91.2%) but lower specificity (42.6%), influenced by factors such as age and smoking prevalence [12].…”
Section: Short Communicationmentioning
confidence: 69%
“…established a cut-off value similar to the value proposed by a previous study [12], which had a sensitivity of 76.5% and specificity of 63.3%. The previous study showed that PUMA scores of ≥5 offered higher sensitivity (91.2%) but lower specificity (42.6%), influenced by factors such as age and smoking prevalence [12]. The AUC of 0.783 highlights the PUMA questionnaire's effectiveness in distinguishing COPD from non-COPD cases among smokers, showing better predictive accuracy than the CAPTURE questionnaire.…”
Section: Short Communicationmentioning
confidence: 69%
See 3 more Smart Citations